Early Millet Use and Its Environmental Impact Factors in Northern Shaanxi, Northwest China - Ma, Zhikun; Liu, Shu; Song, Jincheng; Zhang, Hua; Zhai, Linlin; Huan, Xiujia (Agronomy (Basel), 2023)
Northern Shaanxi is important in understanding the ancient use and northward spread of foxtail millet (Setaria italica) and broomcorn millet (Panicum miliaceum). Nonetheless, due to the lack of millet remains, AMS radiocarbon data, and environmental background, the emergence, crop structure, and environmental factors of millet use in northern Shaanxi remain ambiguous. To address this knowledge gap, a systematic survey was conducted along the Beiluo River. Forty-two relic units at 19 Neolithic sites were selected for analysis through phytolith, AMS radiocarbon dating, and spatio-temporal approaches. Phytolith and AMS radiocarbon dating analyses traced the utilization of millets in the Beiluo River to 6280 cal. BP. In addition, broomcorn millet was more prevalent than foxtail millet during the Neolithic period, although the prevalence of the latter increased during the late Longshan period. Spatio-temporal analysis demonstrated that millets initially appeared in the Beiluo River during the Yangshao period, gradually moving away during the Longshan period, which was probably first related to the nearest rivers and then the spread of cattle and sheep. However, the millet cultivation altitude remained at 1400 m throughout the Yangshao and Longshan periods. Collectively, these findings provide evidence for the use and northward spread of millets in northwest China.